Light: advanced manufacturing (Light Publishing Group, 2020)
Aimed to publish innovative research in all modern areas of preferred light-based manufacturing, including fundamental and applied research as well as industrial innovations.
Keywords: Light : Periodicals; Manufacturing processes : Technological innovations : Periodicals; Optical engineering : Periodicals; Luz; Procesos de fabricación : Innovaciones tecnológicas; Lumière : Périodiques; Fabrication : Innovations : Périodiques; Génie optique : Périodiques; Light; Manufacturing processes : Technological innovations; Optical engineering